Offensive and defensive team performance: relation to successful and unsuccessful participation in the 2010 Soccer World Cup - Delgado-Bordonau, J. L.; Domenech-Monforte, C.; Guzmán, J. F.; Mendez-Villanueva, A. (Journal of Human Sport & Exercise, 2013)
The present study was conducted to analyze the impact of selected offensive and defensive performance indicators in relation to teams` success in the 2010 soccer World Cup. The sample used corresponded to 54 matches played in both the group and knockout stage. The game-related statistics gathered were: total shots, shots on goal, shots off goal, % of shots on goal from total shots , % of shots off goal from total shots, offensive and defensive effectiveness 1 (goals /total shots), and offensive and effectiveness 2 (goals/shots on goal). In addition, the first`s goal influence in the match`s outcome (for the team scoring the goal: win, draw, lose) was also investigated. The results showed that, during the group stage, successful teams had better values (P <0.05) in all offensive and defensive performance indicators, with the exception of shots off goal for and shots off goal against, respectively, than unsuccessful teams. In the knockout stage, successful teams were able to maintain the same offensive performance that in the group stage while most defensive performance indicators, with the exception of shots off goal against (P=0.80), tended (P<0.2) to worsen. During the group stage, the team scoring the first goal had 66.7% of victories, 4.2% of defeats and 29.2% of draws (P<0.001). In the knockout stage, the first goal effect had a stronger influence in game`s outcome than in the group stage (P<0.01) since in 81.3% of the cases the team scoring first won the match, versus 6.3% of defeats and 12.5% of draws. Thus, offensive variables related to shots on goal and goal effectiveness appear to be better indicators of team`s success in the last World Cup than defensive variables. This information has directly implications for coaches, providing relevant feedback to plan finishing (goal scoring) practices.